Dynamic Equilibrium of Marketing and Its Role in Achieving Excellence Performance Experimental research on a number of Iraqi private banks - جثير, سعدون حمود; القيسي, بلال جاسم (Journal of Economics and Administrative Sciences, 2013)
Purpose  :This study seeks to provide the point of view stands on the marketing performance of the banks in the context of Dynamic Equilibrium  of marketing. It aims to develop a prototype of measuring marketing performance under the umbrella of marketing dynamic prototype, embodied of the strategic alliance and competition, and the  laws and legislation, and to explore any of the dimensions more effective in achieving performance.  This study aims to discusses the importance of the Dynamic Equilibrium  of marketing and it role in achieving the marketing performance under Dynamic Equilibrium  of marketing and its impact on the Iraqi banking sector.Design/Methodology/Approach: The experimental method has been used, the questionnaire used to collect the data in order to develop a trustworthy prototype measurement and correct for the changes of the Dynamic Equilibrium  of marketing and customer relationship management With the dimensions of marketing performance, the hypotheses were tested through the use of some statistical treatments.    Findings: The study of the sample found that marketing performance is effected directly in the dynamics of the industry, and the intensity of competition, and the uncertain environment  that includes (degree of predictability in the business environment), a model measuring variables Dynamic Equilibrium  of Marketing has been developing (alliances strategy, competition, legislation/ laws) with marketing performance variables (focus on the customer, focus on the competitors), moreover, the results support the hypothesis influence and correlation between the surveyed  variables.Practical Implications: This study provides useful measurement of marketing balance, it helps the managers to use to assess the current situation in the capabilities of the banks performance. Managers may improve their marketing performance programs more effectively and efficiently through their strategic orientation towards competition and alliance. Originality/ Value : This study undertakes help service providers in banking sector to deal with the challenge imbedded in increase the marketing performance and achieve the dynamic marketing balance, and how to influence the marketing balance dimensions in achieve the marketing performance.